Risk Factor Characteristics Of Patients With Uterine Prolapse In Gynecology Outpatient Clinic In Dr. Soetomo Hospital, Surabaya - Vemaniarti Lian Pravitasari; Eighty Mardiyan Kurniawati; Pirlina Umiastuti (Biomolecular and Health Science Journal, 2021)
Introduction: Uterine prolapse can occurs due to the failure of the ligamentous and fascial supports of the uterus. It causes inconvenience to the patients because of genital tract dysfunction and decrease quality of life. The risk factor are multifactorial. Advancing age, increasing parity, vaginal delivery, and menopause is associated with the uterine risk factors. The aim of this study is to describe the stage, treatment, age, parity, vaginal delivery, and menopause status of women with uterine prolapse in Dr. Soetomo General Academic Hospital, Surabaya. Methods: This research is a descriptive study. The sample is included all women with complaints of uterine prolapse diagnosed and treated at Dr. Soetomo General Academic Hospital, Surabaya from January – December 2017. Statistical was analysed descriptively.Results: From total 82 patients of uterine prolapse in Gynecology Outpatient Clinic Dr. Soetomo General Academic Hospital, Surabaya in 2017, most of the uterine prolapse patients were older than 65 years old (45.1%) and multiparous (62.2%). More than half of the patients (61%) have had more than three vaginal deliveries and have gone through menopause (91.5%). Stage IV prolapse, 33 cases (40.2%) has the highest percentage. Mostly, 47 cases (57.3%) received conservative treatment. Conclusion: Uterine prolapse is most likely to be found in women with older age, came from those in the age group of >65 years old. The incidence of uterine prolapse might increase in multiparous women, have more than three vaginal deliveries, and have gone through menopause. Most of them is on stage IV and received conservative treatment. It is important for women to be educated about uterine prolapse risk factor as an uterine prolapse prevention.